Effect of shield magnetization on variations in the frequency of onboard rubidium atomic clocks - Ermak Sergey; Semenov Vladimir; Baranov Alexey; Rogatin Maxim; Sergeeva Maria (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2024)
In the paper, the results of a study of the influence of the magnetic shield magnetization on the relative frequency instability of small-sized rubidium atomic clocks have been presented. The atomic clock was placed in a rotating magnetic field, simulating the magnetic situation in the orbit of a navigation satellite, moving in orbit and rotating around its own axis. The magnetization of the magnetic shield of the atomic clock was shown to increase its shielding factor. This result makes it possible to significantly reduce the influence of geomagnetic field variations on the frequency stability of onboard atomic clocks.